Penatalaksanaan Kasus Protrusif Gigi Anterior Atas dengan Kelainan Periodontal pada Pasien Dewasa - Yovela Yovela; Krisnawati Krisnawati (Faculty of Dentistry, Universitas Indonesia, 2012)
In the last few years, people from various age group are looking for orthodontic treatment, among them are adult. Adult patients in comparison with children or adolescent, have different condition in regard to their teeth and periodontal tissue. These differences will affect treatment plan we are making for adult patients. Orthodontic treatment for adult patients requires the use of light force, bondable tube and ligature wire. These steps are taken as an effort to overcome chief complaint and to prevent periodontal breakdown. DOI: 10.14693/jdi.v16i1.17